Counteractive Strategies in Colonial and Postcolonial Narratives of Memory: Joseph Conrad’s Heart of Darkness and Anita Desai’s Clear Light of Day - Akhtar, Rizwan (Archīum Ateneo, 2013)
This paper examines the role of memory in colonial and postcolonial literary narratives. In postcolonial and colonial literary discourse, memory spaces are fiercely contested. Joseph Conrad’s Heart of Darkness (1906) and Anita Desai’s Clear Light of Day (1980) are respectively colonial and postcolonial narratives in which indigenous and colonial subjects configure preserving their ways of remembrance. Colonial ways of remembrance collide with indigenous ways of remembrance. The colonial subject imposes its ways of remembrance on indigenous subject. Consequently, the indigenous subject counteracts the colonial ways of remembrance.